GRADING PROCESS OF GOLDEN AROMA MELON COMMODITY IN NAWASENA GREENHOUSE HYDROPONIC IN KARANGNANAS VILLAGE, SOKARAJA DISTRICT, BANYUMAS REGENCY - Fedinda Nara Arsya Pravista; Pujiati Utami (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Horticultural crops play an important role in Indonesian agriculture. One of the horticultural crops that play an important role is melon. Melon (Cucumis melo L.) is one of the horticultural commodities that has a great opportunity to be developed. The economic value of various types of horticulture depends on the quality of these commodities. Therefore, it is necessary to classify products (grading) based on appearance, sweetness level, color, shape, size, weight, maturity level, and others. The purpose of this research was to find out more about the grading process of golden aroma melon commodities at Nawasena Greenhouse Hydroponic in Karangnanas Village, Sokaraja District, Banyumas Regency. The method used in the research is a qualitative method with a descriptive analysis approach. The results showed that the grading process every harvest is by conducting a grading test for each segment of the melon plant or it can be said to be a sample of each segment.